PENGEMBANGAN MEDIA BOOKLET DIGITAL BERBASIS CANVA TEMA "WOHNUNG" UNTUK KETERAMPILAN MEMBACA SISWA KELAS XI SEMESTER GENAP - Wulandari, Dinda; Wahyuningsih, Fahmi (LATERNE, 2025)
Teaching and learning activities will run smoothly if teachers can choose learning media that are in accordance with the development of the times. In today’s era, digital learning media is one of the things that many students are interested in and teachers are interested in applying digital media during learning, of course this also aims to change the learning atmosphere with a new style to make it more fun and not boring. With the many digital media developed in society, digital booklets can also be one of the media choices that can be used during teaching and learning activities. In addition, in learning German which is very complex, it is also undeniable that there is a need for appropriate learning media. So media that is suitable for each of these skills is needed. The method in this study is Research and Development with the ADDIE model which is limited to the third stage, namely Development. The data sources obtained come from media expert validators and material expert validators. While the data obtained comes from the validation sheets of both experts. The data collection technique is carried out using a validation sheet and is analyzed and calculated using the Likert scale formula. The results of the validation sheets of material experts and media experts show that the media developed obtained the same feasibility percentage, namely 94%, so the media is considered very suitable for use as a learning medium, especially for German reading skills.